2021
DOI: 10.1021/acschembio.1c00401
|View full text |Cite
|
Sign up to set email alerts
|

Thermostability of Ctenophore and Coelenterate Ca2+-Regulated Apo-photoproteins: A Comparative Study

Abstract: The stabilities of Ca2+-regulated ctenophore and coelenterate apo-photoproteins, apo-mnemiopsin (apo-Mne) and apo-aequorin (apo-Aeq), respectively, were compared biochemically, biophysically, and structurally. Despite high degrees of structural and functional conservation, drastic variations in stability and structural dynamics were found between the two proteins. Irreversible thermoinactivation experiments were performed upon incubation of apo-photoproteins at representative temperatures. The inactivation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The experiment was conducted in triplicate, with each trial consisting of three measurements. The result presented is the average of these triple measurements [23][24][25].…”
Section: Thermal Inactivation and Thermodynamic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment was conducted in triplicate, with each trial consisting of three measurements. The result presented is the average of these triple measurements [23][24][25].…”
Section: Thermal Inactivation and Thermodynamic Parametersmentioning
confidence: 99%
“…A negative value for entropy changes indicated that the formation of the transition state structure for the untreated uricase enzyme has been accompanied by a decline in the entropy of the system. The decrease in the system's entropy is probably attributable to the organization of more water molecules surrounding the hydrophobic residues that are exposed on the surface during the unfolding process [24,25,42]. and taurine-UOX (black).…”
Section: Thermal Inactivation and Stabilitymentioning
confidence: 99%